Signature-Based & Anomaly-Based Network & Intrusion Detection System (SBNIDS & ABNIDS) - Rene, Chiadighikaobi Ikenna; Johari, Abdullah (Faculty of Computer Science and Information Technology, 2015)
The poster was submitted as part of the UNIMAS R&D Expo 2015. The project won Bronze Medal from the Expo for the ICT Cluster category.